High-Quality Assemblies for Three Invasive Social Wasps from the Vespula Genus. Issue 10 (1st October 2020) - Harrop, Thomas W R; Guhlin, Joseph; McLaughlin, Gemma M; Permina, Elizabeth; Stockwell, Peter; Gilligan, Josh; Le Lec, Marissa F; Gruber, Monica A M; Quinn, Oliver; Lovegrove, Mackenzie; Duncan, Elizabeth J; Remnant, Emily J; et al.
Abstract: Social wasps of the genus Vespula have spread to nearly all landmasses worldwide and have become significant pests in their introduced ranges, affecting economies and biodiversity. Comprehensive genome assemblies and annotations for these species are required to develop the next generation of control strategies and monitor existing chemical control. We sequenced and annotated the genomes of the common wasp ( Vespula vulgaris ), German wasp ( Vespula germanica ), and the western yellowjacket ( Vespula pensylvanica ). Our chromosome-level Vespula assemblies each contain 176–179 Mb of total sequence assembled into 25 scaffolds, with 10–200 unanchored scaffolds, and 16, 566–18, 948 genes. We annotated gene sets relevant to the applied management of invasive wasp populations, including genes associated with spermatogenesis and development, pesticide resistance, olfactory receptors, immunity and venom. These genomes provide evidence for active DNA methylation in Vespidae and tandem duplications of venom genes. Our genomic resources will contribute to the development of next-generation control strategies, and monitoring potential resistance to chemical control.